2021
DOI: 10.24911/ijmdc.51-1623238530
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of ear, nose, and throat disease seen by otolaryngologists at Qassim University outpatient clinics, Saudi Arabia

Abstract: Background: Ear, nose, and throat infections are serious public health concerns affecting patients of all ages. They can affect hearing difficulties, speech, phonation, breathing, swallowing, smell, taste, and other respiratory tract infections. This study aimed to determine the pattern of otolaryngological head and neck diseases seen at Qassim University outpatient clinics, Saudi Arabia. Methodology: This descriptive retrospective study was conducted in outpatient clinics at Qassim University, Saudi Arabia. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In this study, the age group of 10-30 years had the most common ENT problems, which accounted for 25% of the total cases. This result is consistent with many studies done by Alhazmi et al and Hannaford et al 9,12 Ear problems were the most common among ENT problems, followed by throat and nose problems. Chijikoe et al found a similar outcome in their study, where the prevalence of ear disease was followed by throat and nose.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the age group of 10-30 years had the most common ENT problems, which accounted for 25% of the total cases. This result is consistent with many studies done by Alhazmi et al and Hannaford et al 9,12 Ear problems were the most common among ENT problems, followed by throat and nose problems. Chijikoe et al found a similar outcome in their study, where the prevalence of ear disease was followed by throat and nose.…”
Section: Discussionsupporting
confidence: 93%
“…Acute tonsillitis (36.7%) was the most common throat disorder in this study, while Alhazmi et al found laryngitis as the most common throat disorder, and Singh A et al found pharyngitis as the most common throat problem. 12,15 The variation in this context can be explained by different regions, environmental factors, overcrowding, nutritional deficiencies, financial constraints, negligence of health, and cold and dry weather of high altitude. Chronic rhinitis and allergic rhinitis were the other leading causes of nose disorders, and extreme cold weather, dry climate, and allergens in the high altitude of the Himalayan part of Nepal could be probable reasons for such high incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Otolaryngology is a medical field focusing on the ears, nose, and throat. It also includes head and neck surgery [ 10 ]. Collagen is the most abundant protein in the extracellular matrix in mammals.…”
Section: Introductionmentioning
confidence: 99%